Developing Engineering Thinking in Students through Solving Geometric Problems - Eshmurodov Axmadjon Nurmuradovich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Annotation: This article examines the pedagogical and methodological foundations for developing engineering thinking in students through the process of solving geometric problems. The study highlights the role of geometry as a key subject that fosters spatial imagination, analytical reasoning, and logical problem-solving abilities. It explores how task-based learning, visualization techniques, and modern information and communication technologies can be integrated into geometry lessons to enhance students’ cognitive activity. Special attention is given to the relationship between geometric thinking and engineering creativity, emphasizing how problem-solving in geometry nurtures the ability to model, analyze, and design real-world objects. The research also discusses effective teaching strategies that encourage independent exploration and critical analysis, ultimately contributing to the formation of a modern, technically literate learner ready for professional challenges in the fields of science, technology, and engineering.